HUBUNGAN KONSUMSI SUSU DAN KALSIUM DENGAN DENSITAS TULANG DAN TINGGI BADAN REMAJA - Hardinsyah Hardinsyah; Evy Damayanthi; Wirna Zulianti (Jurnal Gizi dan Pangan, 2008)
The objective of this study was to analyze the relationship between milk and calcium intake with body height and bone density of adolescent. The study applied a cross sectional design to 246 senior high school students in Bogor. The subject aged 16-17 years old were selected purposively. Milk and calsium intake was derived from the food intake data collected by applying a semi-FFQ method for a week. Bone density (stiffness index) was measured by densitometer of achilles insight. The results of the study showed that the mean intake of milk was 170.7±136.3 ml/day with average frequency 6 times/week, and mean intake of calcium was 250.0±212.6 mg/day with contribution of milk was 44.0%. The mean stiffness index of subjects was 97.5±18.3; and the mean stiffness index of boys (104.4±18.9) was significantly higher than girls (92.9±16.3). The calcium intake of milk and calcium intake of calsium-rich foods of non milk was not correlated with the bone density and body height; but milk intake,  frequency and  length of milk intake were correlated with body height and bone density. This implies the important of milk intake in bone density and  linear growth of adolescent.